Older patients with Hodgkin Lymphoma: Walking the tightrope of efficacy and toxicity - Barrett, Aisling; Collins, Graham P. (Frontiers in Oncology, 2023)
Since its initial description, classical Hodgkin lymphoma (cHL) portends a greatly improved prognosis and the goal of treatment in most patients is cure with minimisation of toxicity from treatment. Outcomes in older patients (>60 years old) lag behind those of their younger counterparts however, and cure remains achievable mostly for those who can tolerate full doses of conventional chemotherapy. This review addresses the difference in biology between younger and older patients with cHL and examines the impact of frailty and comorbidities on outcomes. The toxicities of conventional chemotherapy in anthracycline-fit and -unfit patients are examined, with a particular focus on pulmonary toxicity associated with bleomycin in older patients. New advances are discussed, including the possibility of using more targeted therapies such as the anti-CD30 antibody brentuximab vedotin (BV) and checkpoint inhibitors as a method of reducing dependency on conventional chemotherapy for those less well able to tolerate it. Treatment of older patients with cHL remains an area of unmet need in hematological research, and efforts to rectify this knowledge gap should continue.